Statistical analysis plan for the EuroHYP-1 trial: European multicentre, randomised, phase III clinical trial of the therapeutic hypothermia plus best medical treatment versus best medical treatment alone for acute ischaemic stroke - Winkel, Per; Bath, Philip M.W.; Gluud, Christian; Lindschou, Jane; van der Worp, H. Bart; Macleod, Malcolm R.; Szabo, Istvan; Durand-Zaleski, Isabelle; Schwab, Stefan (BioMed Central, 2017)
Background: Cooling may reduce infarct size and improve neurological outcomes in patients with ischaemic stroke. In phase II trials, cooling awake patients with ischaemic stroke has been shown to be feasible and safe, but the effects in functional outcomes has not yet been investigated in an adequately sized randomised clinical trial. Methods/design: The EuroHYP-1 trial is a multinational, randomised, superiority phase III clinical trial with masked outcome assessment testing the benefits and harms of therapeutic cooling in awake adult patient with acute ischaemic stroke. The outcomes dealt with here include the primary outcome the Rankin score (mRS) at day 91 +/-14 days after randomisation. The secondary and exploratory outcomes at day 91 +/-14 days unless otherwise stated encompassing: (1) death or dependency, defined as mRS score > 2; (2) death; (3) National Institutes of Health Stroke Score; (4) brain infarct size at 48 +/-24 hours; (5) EQ-5D-5 L score, and (6) WHODAS 2.0 score. Other outcomes are: the primary safety outcome serious adverse events; and the incremental cost-effectiveness, and cost utility ratios. The analysis sets include (1) the intention-to-treat population, and (2) the per protocol population. The sample size is estimated to 800 patients (5% type 1 and 20% type 2 errors). All analyses are adjusted for the protocol-specified stratification variables (nationality of centre), and the minimisation variables. In the analysis, we use ordinal regression (the primary outcome), logistic regression (binary outcomes), general linear model (continuous outcomes), and the Poisson or negative binomial model (rate outcomes). Discussion: Major adjustments compared with the original statistical analysis plan encompass: (1) adjustment of analyses by nationality; (2) power calculations for the secondary outcomes; (3) to address the multiplicity problem using of a fixed-sequence testing procedure starting with the primary outcome followed by the secondary outcomes ordered according to falling power; (4) assignment of worst possible score to patients who are not alive at the planned date of measurement of the continuous scores; (5) improved imputations; (6) outline of a supplementary exploratory analysis of the temperature measurements and time to death; and (7) substantial reduction of sample size. Trial registration: Clinicaltrials.gov, identifier: NCT01833312. 4 April 2013.